PEMBERIAN BANTUAN HUKUM TERHADAP APARATUR SIPIL NEGARA (ASN) PELAKU TINDAK PIDANA KORUPSI PADA PENGADILAN TINDAK PIDANA KORUPSI DENPASAR - Kadek Mery Herawati (Universitas Mahendradatta, 2022)
The right of the suspect to obtain legal assistance is a fundamental right guaranteed by law and the state to the suspect, applicable to all criminal legal processes, so that fair legal provisions are reached for the suspect, victim, and the community as a whole. When a State Civil Apparatus (ASN) is trapped in legal issues, the State should be present to defend by considering the principle of presumption of innocence. The objective to be achieved in this study is to provide legal understanding to the public regarding legal aid and sanctions for ASN who commit acts of corruption. Theories used in this research are Legal Certainty Theory and Justice Theory. The research method used is a juridical-normative research method. The results showed that the Legal Aid and Sanction Arrangements for ASN have been regulated in the Law of the Republic of Indonesia Number 5 of 2014 concerning State Civil Apparatus. However, sanctions against ASN have not been able to fulfill the legal ideals of justice, expediency, and legal certainty. This is because the substance of the formulation of Article 87 Paragraph (2), Article 87 Paragraph (4) letters b and d, Article 92 Paragraph (3) of the Law of the Republic of Indonesia Number 5 of 2014 concerning State Civil Apparatus, Jo Article 250 letters b and d Republic of Indonesia Government Regulation Number 11 Year 2017 Regarding Management of Civil Servants, Multiple Interpretations, raises doubts, obscurity, ambiguity, confusion, or has multiple meanings